Jobseekers' beliefs about comparative advantage and (mis)directed search - Andrea Kiss; Robert Garlick; Kate Orkin; Lukas Hensel (W.E. Upjohn Institute for Employment Research, 2023)
Worker sorting into tasks and occupations has long been recognized as an important feature of labor markets. But this sorting may be inefficient if jobseekers have inaccurate beliefs about their skills and therefore apply to jobs that do not match their skills. To test this idea, we measure young South African jobseekers' communication and numeracy skills and their beliefs about their skill levels. Many jobseekers believe they are better at the skill in which they score lower, relative to other jobseekers. These beliefs predict the skill requirements of jobs where they apply. In two field experiments, giving jobseekers their skill assessment results shifts their beliefs toward their assessment results. It also redirects their search toward jobs that value the skill in which they score relatively higher - using measures from administrative, incentivized task, and survey data - but does not increase total search effort. It also raises earnings and job quality, consistent with inefficient sorting due to limited information.
Keywords: C93; D83; J24; J31; O15; 330; jobseekers; worker matching; skills; beliefs; search effort; field experiments; South Africa